La planificación financiera y su incidencia en la gestión administrativa de las PYMES de la ciudad de Echeandía, año 2019 - Chimbo Hidalgo, Jonathan Israel (2020)
This research work was developed with the purpose of knowing the situation with which SMEs are managed based on financial planning and administrative management, which are dedicated to commercial activities. SMEs are the engine of economic development in the country, so they deserve greater attention when conducting their economic activities, therefore, business behavior was studied and it was determined that they should permanently apply financial planning in the administrative management that allows the development and economic growth of the different businesses. Financial planning is considered to be the fundamental basis at the time of starting commercial activities, it allows for an equitable distribution of the resources that an institution has. In the research, the methodology comprising descriptive, field and bibliographic research was applied, which served as a method for obtaining and collecting information, using the methods and techniques of research instruments. Keywords: Financial Planning, Administrative Management, SMEs, Economics